Establishment of fingerprint of phenolic compounds in Semen Ziziphi Spinosae and study on the spectrum-effect relationship based on different preceding cropping areas - Jiang, Junfeng; Luo, Jun; Zheng, Wenyu; Liu, Jiayi; Jiang, Hui; Wu, Cuiyun; Bai, Hongjin (Frontiers in Chemistry, 2025)
As an agricultural planting practice, preceding cropping can not only enhance soil fertility and reduce pests and diseases but also boost crop yield and quality. In this study, SZS samples from different preceding cropping areas were selected as research subjects. Phenolic compounds were analyzed using high-performance liquid chromatography (HPLC), and antioxidant activities were assessed based on free radical scavenging effects. Variety differences were explored through chemical pattern recognition, and the spectrum-effect relationship between the fingerprint spectra of SZS and antioxidant activity was investigated using Pearson correlation analysis, grey relational analysis, and other methods. A total of 17 peaks were observed, among which 4 peaks were identified. They are gallic acid, catechin, spinosin, and scutellarin. The 22 SZS samples could be categorized into 3 groups, with cluster analysis and principal component analysis results being largely consistent. Spinosin, a marker compound of SZS, is a crucial contributor to the total antioxidant activity. In conclusion, the spectrum-effect relationship between phenolic compounds and the antioxidant activity of SZS was established, and the main characteristic components affecting antioxidant activity were identified, providing a reference for the quality evaluation of SZS and the development of its products.